2012
DOI: 10.1111/j.1460-9568.2012.08053.x
|View full text |Cite
|
Sign up to set email alerts
|

Auditory perception and syntactic cognition: brain activity‐based decoding within and across subjects

Abstract: The present magnetoencephalography study investigated whether the brain states of early syntactic and auditory-perceptual processes can be decoded from single-trial recordings with a multivariate pattern classification approach. In particular, it was investigated whether the early neural activation patterns in response to rule violations in basic auditory perception and in high cognitive processes (syntax) reflect a functional organization that largely generalizes across individuals or is subject-specific. On … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 68 publications
2
8
0
Order By: Relevance
“…The present cross-participant analyses provide additional support for this view. They are also in line with previous cross-participant classification analyses presented in [33], [35], which showed either equivalent or improved classification performance when using cross-participant data sets as compared to within-participant datasets. As was the case with the results presented in [33], the overall improvement in performance here may be due to the increased amount of training data available in the cross-participant analysis.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The present cross-participant analyses provide additional support for this view. They are also in line with previous cross-participant classification analyses presented in [33], [35], which showed either equivalent or improved classification performance when using cross-participant data sets as compared to within-participant datasets. As was the case with the results presented in [33], the overall improvement in performance here may be due to the increased amount of training data available in the cross-participant analysis.…”
Section: Discussionsupporting
confidence: 91%
“…Within-participant single-trial classification rates were comparable with the average rates reported in [35]. The results of that study also showed a graded pattern of results depending on which manipulation (auditory space, syntax or both) was present in the experimental stimulus.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This suggests that activity in and around this frequency band will provide discriminative information for the present classification analysis. Other studies classifying MMN data (Herrmann et al, 2012) and auditory evoked responses to music (Schaefer et al, 2011) have also made use of similar filter settings during preprocessing, indicating that band-pass filtering in the 0.5–13 Hz range might improve decoding performance for auditory brain responses.…”
Section: Single-trial Decoding Of Auditory Erps Containing the Mmnmentioning
confidence: 99%
“…It is wrong to put pressure on them because it makes them feel that they have failed and are unable to perceive and discriminate, as they are in need of special means to help them with their learning (Filippini, et al 2013). Perceptual processes are considered prerequisites to learning to read, because developmental learning difficulties represented in the synthesis of sounds (auditory perception) are one of the main reasons that prevent a child from learning to read (Herrmann, 2012; Al-Bashtawy et al, 2014).…”
Section: Social Difficultiesmentioning
confidence: 99%